KERAGAMAN KARAKTER MORFOLOGI BAKTERI INDIGENOUS YANG DIISOLASI DARI LENDIR KATAK SAWAH (F. CANCRIVORA) LOKAL PADA BAGIAN DORSAL DAN VENTRAL - Lela Susilawati; Afrizka Premana Sari (Kaunia: Integration and Interconnection Islam and Science, 2013)
F. cancrivora is an abundance species in Indonesia. It is believed that indigenous bacteria isolated from F. cancrivora have many bioactive substances. Different habitat of F. cancrivora will influence the bacteria lived in their mucous. Hence, comparing the morphological properties among them is one of preliminary assay to explore their potential as bioactive substances’ producer. The present work explored the diversity of morphological characteristic of indigenous bacteria isolated from skin mucous of F. cancrivora. The bacteria were isolated from dorsal and ventral skin mucous using swab method. The colonies that appeared on nutrient agar were then purified and characterized based on the colony and cell properties. A total 20 isolates were obtained, 11 of them are from dorsal site and 9 isolates are from ventral site. The morphological characteristic of those isolates showed that the bacteria isolated from dorsal site have higher diversity in term of colonies and cell characteristic than bacteria isolated from ventral site of frog skin mucous.